Impact evaluation of education on poverty in Costa Rica (An analysis for secondary and postsecondary education) - Sánchez Retana, Carmen (2015)
This research evaluates the impact of education on poverty in Costa Rica. Specifically, the impact on the probability of being poor of a person that finishes secondary education (highest educational level attained). Furthermore , the impact for a person which has at least this level of education (possibility of post- secondary studies). Using Propensity Score Matching methodology and the survey Encuesta Nacional de Hogares 2013, results show positive impact of education in reducing poverty. When an average person completes the full secondary education reduces the probability of being in poverty by 5.7 percentage points, representing a decrease in poverty rates of those who have completed secondary in 21.1%. Meanwhile, with the possibility of post-secondary studies, the probability is reduced by 8.4 percentage points. Amount equivalent to a 36.8% decline in poverty rate of individuals who have at least completed secondary education.